Young SNP members: socio-nationalism, identity and politics - Breniaux, Claire (Frontiers in Political Science, 2024)
Scotland is an interesting case study when it comes to politics, nationalism and identity. The separatist movement led by the Scottish National Party (SNP) raises a wide range of questions with regard to Scottish and British politics as well as people's sense of belonging. Given that young people are the generation most likely to witness a hypothetical second independence referendum in the future, this paper focuses on them. It examines the young members of the SNP. It explores the interconnection between Scottish politics and young SNP members' nationalism as well as their understanding of Scottishness. With the analysis of empirical research conducted from 2018 to 2020, it suggests that the Young Scots for Independence (YSI) and SNP Students' nationalism should be regarded as socio-nationalism. This paper defines it as the promotion of societal values and a certain perception of society combined with the promotion and defense of a nation. Interviews and questionnaires reveal that these young people define Scotland as socially just, equal and open. Overall, their definition of Scottishness is similar. In that sense, this paper argues that their political ideology and their sense of belonging are interrelated. This is highlighted by the fact that Scottish independence is, among other factors, the most significant reason why young people choose to become SNP members. It also highlights a relationship between their sense of Scottishness and their wish for Scotland to become independent. Therefore, this paper argues that young people's membership of the SNP and national identity are interrelated.